2002
DOI: 10.1191/1352458502ms839oa
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in multiple sclerosis: a comparison of different rating scales and correlation to clinical parameters

Abstract: The association of fatigue and depression suggests that there might be either common underlying mechanisms or interdependence by a cause-and-effect relationship that requires further investigation. The weak correlation within various fatigue scales is best explained by the fact that fatigue is a multidimensional symptom and, therefore, the available tests measure and weight different aspects of fatigue. Our findings underline the necessity for a more exact definition of fatigue and the development of more vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
405
5
30

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(464 citation statements)
references
References 20 publications
24
405
5
30
Order By: Relevance
“…The HADS and FSS have been previously validated in MS and CFS studies. [20][21][22][23][24] The effect of the exercise specifically on fatigue and pain was monitored using two separate visual analogue scales (VASs). The scales were 10 cm in length anchored between 0 (no pain/fatigue) and 10 (most severe pain/ fatigue imaginable).…”
Section: Screening and Outcome Measuresmentioning
confidence: 99%
“…The HADS and FSS have been previously validated in MS and CFS studies. [20][21][22][23][24] The effect of the exercise specifically on fatigue and pain was monitored using two separate visual analogue scales (VASs). The scales were 10 cm in length anchored between 0 (no pain/fatigue) and 10 (most severe pain/ fatigue imaginable).…”
Section: Screening and Outcome Measuresmentioning
confidence: 99%
“…1,5,8,16,17 The items are measured using a seven-point Likert scale ranging from one (strongly disagree) to seven (strongly agree). The items were summed and a mean score was calculated.…”
Section: Measurementmentioning
confidence: 99%
“…1 It is important to investigate fatigue because it has been shown to have an impact across all domains of function and can negatively affect daily and social activities and quality of life. 1,6 Fatigue as a clinical issue has been studied in many diseases and disorders such as multiple sclerosis, [7][8][9] Parkinson's disease 1 and stroke. 6 Studies in Parkinson's and stroke have shown that fatigue can be distinguished from depression both in samples that have and have not controlled for depression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, most outpatient rehabilitation programs emphasize improvements in functional status, but such improvements may not be the most important sign of the success of an intervention program. Many researchers investigating MS patient population characteristics study constructs such as fatigue, [14][15][16][17] depression, 4,16 somatization, 5,11,13,34 self-efficacy, 17,33 fear, 10 pain, 30 and functional status. However, these constructs should not be considered independent.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, depression and somatization 11 are recognized as common confounders of clinical outcomes, 12 including in people with MS. 4 The point prevalence of major depression may be as high as 17% in patients seen by primary-care providers, yet some believe the prevalence of depressive disorders in people with MS is much higher. The prevalence of somatization is difficult to assess, but it is common in people with MS. 5,13 Likewise, fatigue is common in people with MS. 14 Fatigue is a complex clinical phenomenon, 15 in part because it is associated with depression, 16 physical functioning, and self-efficacy. 17 A rapid screening tool, the Modified Fatigue Impact Scale (MFIS), was selected.…”
Section: Participants and Settingmentioning
confidence: 99%